Risk factors for glucocorticoid induced osteoporosis in young adults - Florez, Helena; Carrasco, Josep Lluis; Barberá, Martina; Hernández-Rodríguez, José; Muxi, Africa; Mocritcaia, Anastasia; Prieto-González, Sergio; Cid, Maria C.; Monegal, Ana; Guañabens, Núria; Peris, Pilar (Frontiers in Endocrinology, 2025)
IntroductionGlucocorticoid-induced osteoporosis (GIOP) is one of the most frequent causes of secondary osteoporosis, especially in young subjects. However, current research and guidelines have scarcely addressed the therapeutic approach and risk factors for GIOP in adults less than 50 years of age. The aim of the study was to analyze if factors related to the development of glucocorticoid-induced osteoporosis (GIOP) and fragility fractures (FF) differ according to age.Methods127 patients on chronic glucocorticoid (GC) treatment were analyzed, including GC doses and duration, disease activity, FF, anthropometric data, bone metabolism parameters (including sex steroids), bone mineral density, trabecular bone score, and radiologic vertebral fractures; defining GIOP as densitometric osteoporosis and/or FF. Young subjects (<50 years old) were compared with those ≥50 years for risk factors of GIOP and FF.ResultsGIOP prevalence was similar in both age groups: <50 (n=36) 44.4% vs. 46.1% ≥50 years (n=91). Five subjects <50 (13.9%) and 30 ≥50 years (33%) presented FF (p=0.046). Having a higher body mass index (BMI), disease activity was a differential risk factor for FF in young subjects, whereas hypogonadism was a risk factor independent of age.ConclusionsMore than 40% of young subjects on chronic GC therapy had GIOP. A higher BMI and disease activity and particularly, hypogonadism seem to be factors related to FF development in these subjects. Evaluation of these risk factors can improve the identification of young subjects at increased risk of fracture.